Intermediation in policy and politics: rethinking the architecture and process of governance - Eitan, Avri; Levi-Faur, David; Tosun, Jale (Policy and society, 2025)
This article introduces the multifaceted roles of intermediaries in policy and governance processes. Intermediaries are organizations and actors that bridge the gap between the public and private sectors. They help resolve conflicting interests, transfer knowledge across different sectors and organizational levels, and facilitate policy coordination and collaboration in complex institutional environments. While certain types of intermediaries have long been recognized as important actors in policy systems, their functions and conceptualization remain inadequately understood. We argue that intermediaries fulfill distinctly different functions depending on their position within various stages of the policy process and the specific governance contexts in which they operate. These functional variations significantly influence policy outputs and outcomes, and governance effectiveness, yet current scholarship lacks sufficient empirical depth to fully conceptualize these differences. To address this gap and facilitate improved theoretical understanding of intermediary functions across diverse policy stages and governance settings, we need to substantially expand our empirical knowledge base. This special issue contributes to this objective by presenting comprehensive case studies and comparative analyses that illuminate the complex, context-dependent nature of intermediary roles, thereby laying crucial groundwork for future conceptual development in this emerging field. Drawing on eight original case studies, it shows how intermediaries act as translators, negotiators, and strategic actors across varied institutional landscapes. Together, the contributions illuminate the relational, contested, and performative dimensions of intermediary work, challenging technocratic accounts, and offering a powerful lens for understanding contemporary governance.
Veröffentlicht: 24. Oktober 2025
Gesehen am 04.12.2025